KAJIAN SOSIOLOGI SASTRA DALAM CERPEN GUNA-GUNA TERUNA KARYA IGG DJELANTIK SANTHA - Ni Wayan Sudiartini (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Abstract This study examines the short story Guna-Guna Teruna through a sociological approach to literature to reveal the relationship between literary works and the social reality that underlies them. The focus of this study includes the analysis of social structures, cultural values, and social conflicts depicted in the short story. The research method used is a qualitative descriptive method with content analysis techniques. The results of the study show that the short story Guna-Guna Teruna reflects social phenomena in society, such as belief in mysticism, the dynamics of social relations, and the influence of customary norms on individual life. In addition, this short story also describes the tension between tradition and modernity in society. This study is expected to provide a deeper understanding of the interaction between literature and social life, as well as enrich the study of the sociology of literature in the context of Indonesian literature. Keywords: sociology of literature, short story, witchcraft, cultural values, social conflict.